Barriers to consumer self-protection in the moneylending decision process in Klang Valley, Malaysia - Sandhu, Daljit Kaur; Muhammad Arif, Afida Mastura; Abu Bakar, Elistina; Abdul Rahim @ Abdul Wahab, Husniyah (Malaysian Consumer and Family Economics Association, 2020)
Licensed moneylending industry supports the credit need of Malaysian consumers who have been denied personal loans by the formal banking sector. This research aims to gain insights into the barriers to consumer selfprotection in the moneylending decision process, fortified by the five-step Consumer Decision Process Model. Qualitative research through phenomenology was employed where 14 borrowers were interviewed. Steps taken to analyze the data was done via coding, categorizing and thematizing using the NVivo version 12 software. Based on the research objective, five related areas which were hindering consumers in achieving self-protection were discovered. They were desperation for funds, reliance on friends for moneylender’s information, indifferent attitude towards evaluating alternative contract options, passive role in contract rights and obligations, as well as the reluctance to file complaints. In overcoming these barriers, the Ministry of Housing and Local Government could educate consumers on the concept of lawful moneylending process, importance and benefits of self-protection practices. Furthermore, consumers need to enrich their financial acumen in preparation for the forthcoming wave of online and mobile money lending.